Risk factors for spread of primary adult onset blepharospasm: a multicentre investigation of the Italian movement disorders study group. Issue 5 (1st November 1999) - Defazio, Giovanni; Berardelli, Alfredo; Abbruzzese, Giovanni; Coviello, Vincenzo; Carella, Francesco; De Berardinis, Maria T; Galardi, Giuseppe; Girlanda, Paolo; Maurri, Silvio; Mucchiut, Marco; Albanese, Alberto; Basciani, Mario; et al.
Abstract : OBJECTIVES: Little is known about factors influencing the spread of blepharospasm to other body parts. An investigation was carried out to deterrmine whether demographic features (sex, age at blepharospasm onset), putative risk, or protective factors for blepharospasm (family history of dystonia or tremor, previous head or face trauma with loss of consciousness, ocular diseases, and cigarette smoking), age related diseases (diabetes, hypertension), edentulousness, and neck or trunk trauma preceding the onset of blepharospasm could distinguish patients with blepharospasm who had spread of dystonia from those who did not. METHODS: 159 outpatients presenting initially with blepharospasm were selected in 16 Italian Institutions. There were 104 patients with focal blepharospasm (mean duration of disease 5.3 (SD 1.9) years) and 55 patients in whom segmental or multifocal dystonia developed (mainly in the cranial cervical area) 1.5 (1.2) years after the onset of blepharospasm. Information was obtained from a standardised questionnaire administered by medical interviewers. A Cox regression model was used to examine the relation between the investigated variables and spread. RESULTS: Previous head or face trauma with loss of consciousness, age at the onset of blepharospasm, and female sex were independently associated with an increased risk of spread. A significant association was not found between spread of dystonia and previous ocular diseases, hypertension, diabetes, neck or trunk trauma, edentulousness, cigarette smoking, and family history of dystonia or tremor. An unsatisfactory study power negatively influenced the validity and accuracy of the negative findings relative to diabetes, neck or trunk trauma, and cigarette smoking. CONCLUSIONS: The results of this exploratory study confirm that patients presenting initially with blepharospasm are most likely to experience some spread of dystonia within a few years of the onset of blepharospasm and suggest that head or face trauma with loss of consciousness preceding the onset, age at onset, and female sex may be relevant to spread. The suggested association between edentulousness and cranial cervical dystonia may be apparent because of the confounding effect of both age at onset and head or face trauma with loss of consciousness. The lack of influence of family history of dystonia on spread is consistent with previous findings indicating that the inheritance pattern is the same for focal and segmental blepharospasm.